2019
DOI: 10.3390/ijerph16224361
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Organic Pollutants in Food: Contamination Sources, Health Effects and Detection Methods

Abstract: Persistent organic pollutants (POPs) present in foods have been a major concern for food safety due to their persistence and toxic effects. To ensure food safety and protect human health from POPs, it is critical to achieve a better understanding of POP pathways into food and develop strategies to reduce human exposure. POPs could present in food in the raw stages, transferred from the environment or artificially introduced during food preparation steps. Exposure to these pollutants may cause various health pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
127
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(128 citation statements)
references
References 204 publications
(248 reference statements)
0
127
0
1
Order By: Relevance
“…e most important route of human exposure to POPs is the consumption of food, especially those of animal origin. Some studies have identified the presence of POPs in oils and fats, meat, eggs, milk, and fish from freshwater ecosystems [38,[80][81][82].…”
Section: Persistent Organic Pollutants (Pops)mentioning
confidence: 99%
“…e most important route of human exposure to POPs is the consumption of food, especially those of animal origin. Some studies have identified the presence of POPs in oils and fats, meat, eggs, milk, and fish from freshwater ecosystems [38,[80][81][82].…”
Section: Persistent Organic Pollutants (Pops)mentioning
confidence: 99%
“…Known TICs include a wide range of persistent legacy and emerging compounds and as such are ubiquitous in the environment, meaning that virtually all humans and wildlife are exposed. Exposure to TICs is unintentional, and environmental or dietary preferences can have a large impact on the overall chemical intake [60][61][62][63][64][65][66][67][68][69][70][71][72]. Effects of TICs will be dependent on both the dynamic regulation of the SMT system during development [13,14,[73][74][75][76], and the modulated transporter activities due to polymorphism in specific ethnic populations [77,78].…”
Section: Transporter-interfering Chemicals and Their Conserved Modes mentioning
confidence: 99%
“…Today, the production of PCBs is banned and industrial emissions of dioxins are limited. However, they still contaminate food by bio-amplification in the food chain and are concentrated in fatty foods due to their low degradability (Guo et al, 2019). It was reported that average daily exposure to TCDD (the most toxic dioxin congener that includes the coplanar PCBs) was below the tolerable daily intake (TDI) dose but it was up to 80 ng/kg body weight per day for non-coplanar PCBs thus exceeding the toxicological reference values for certain groups of consumers (Baars et al, 2004, EFSA, 2005.…”
Section: Introductionmentioning
confidence: 99%